Acute fuelling and refuelling practices of male academy soccer players: implications for physical development and performance - Stables, R.; Hannon, M.; Costello, N.; Close, G.; Morton, J. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: The energy expenditure of male adolescent soccer players [1] from the English Premier League (EPL) is comparable to (or greater) than adult players [2]. Given the requirement to promote growth and maturation in this population, there is a necessity for players to consume sufficient energy and macronutrient intake (EI) in the hours before and after training. "Under-fuelling" at this time is likely to reduce training performance and may increase the risk of injury to bone and tendinous structures. Accordingly, the aim of this study was to quantify the EI of male adolescent soccer players in the four hours pre- and post-training.